Análisis cinemático del lanzamiento con el brazo derecho e izquierdo en waterpolo - Aragón Vela, J.; Fernández Santos, J.; Gómez Espinosa de los Monteros, R.; Carrasco Peña, A.; Mora Vicente, J.; González Montesinos, J.L . (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2010)
The present work analyzed the differences in the Speedy of throwing between right and left top member. 16 players of water polo participated (24.25±4.8 years, 1.97±1.9 m, 75.33±7.1 Kg). They carried out a warm up, both general and specific, to perform 3 throwings with each arm. Speed of throwing was calculated through 2D photogrammetry. Results suggests that there are significant different between right and left top member ( = 18.66 ± 3.047 m/s y = 12.06 ± 1.476 m/s, respectively) and a high correlation (p<0.01) between age and differences in throwing between both arms.